O fragmentaryzacji srebra wczesnośredniowiecznego: na ile wiarygodne są dane metrologiczne? Przypadek skarbu z Mózgowa na Warmii (t.p.q. 1009) - Bogucki, Mateusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
For years, a discussion has been held about the circulation of silver in the early Middle Ages and the role played by fragments of coins and ornaments. This multi-faceted discussion has also revolved around the function of the smallest fragments. Metrological research has indicated certain regularities in the incidence of fragments of a specified weight depending on region and chronology. New data for this discussion was provided by a treasure trove originally discovered in 1868 in Mózgowo in Warmia. Only slightly more than 400 coins have survived from the items discovered in the 19th century; they are a part of a collection of the Herzog Anton Ulrich Museum in Braunschweig. The place where the treasure was discovered was identified in 2010; more than 800 coins and fragments thereof were unearthed. In 2012, the area was examined as a site of excavation where subsequently over 370 specimens were discovered. The treasure trove must have been hidden sometime after 1009, most probably around 1015. The coins from the museum in Braunschweig are not suitable for metrological analysis because they were intentionally separated for a systematic collection. Following an analysis of the specimens discovered in 2010 and 2012, considerable discrepancies in weight frequencies were observed. It turns out that in the collection of objects excavated by professional metal detector operators, very small fragments of silver prevail. Before, they were rarely registered in early medieval treasures (fragments weighing more than 1 gram represent only 6.66%, pieces weighing less than 1 g represent 93.33%, fragments of up to 0.5 g represent 87.61%, while pieces weighing less than 0.1 g represent a whopping 55% of the entire collection).The differences in the weight of silver fragments in the specific parts of the treasure trove from Mózgowo shed new light on both the methodology of examining treasure troves and how representative the data used so far in statistical and metrological analyses are.